Academic resilience and the perceived use of generative artificial intelligence among dental students at Universitas Ciputra Surabaya - Olivia Budihargono; Gabriela Halim (Indonesian Journal of Dental Medicine, 2026)
Background: In the digital age, especially in Indonesia, generative artificial intelligence (Gen AI) is expanding quickly and has enormous potential to enhance dental education. Digital technology facilitates personalized learning, case simulation, and clinical comprehension. One example of adaptive learning is online education. This flexibility promotes the application of Gen AI in education. The perceived value of Gen AI is thought to improve students’ academic resilience in the face of stress and learning shifts. But it’s still unclear how they relate, especially to dental students who have demanding coursework. Purpose: To investigate dental medicine students’ academic resilience and their perception of Gen AI’s utility. Methods: A Likert-scale questionnaire was used in this study’s quantitative cross-sectional design, and Partial Least Squares Structural Equation Modeling (PLS SEM) was used for analysis. Total sampling was used to include all enrolled dentistry students at Universitas Ciputra Surabaya (n = 36). Active students and prior use of Gen artificial intelligence (AI) were prerequisites for inclusion. Students with incomplete responses or those on academic leave were not included. Results: The average academic resilience score was 4.067 ± 0.83, and the average perceived usefulness score was 4.232 ± 0.85. Academic resilience was significantly predicted by perceived usefulness (β = 0.544; t = 2.612; p < 0.01), accounting 29.6% of its variance (R² = 0.296). Conclusion: Dental medicine students’ academic resilience in the digital age was substantially correlated with their perception of Gen AI’s utility. AI integration could improve dental education and help dental medicine students succeed academically.